Imaging findings of Gorlin-Goltz syndrome. Issue 1 (6th January 2015) - Hajalioghli, Parisa; Ghadirpour, Ali; Ataie-Oskuie, Reza; Kontzialis, Marinos; Nezami, Nariman
A 15-year-old girl was referred to a dentist complaining of parageusia, bad taste in the mouth, which started 9 months ago. Panoramic X-ray and non-enhanced computed tomography scan revealed multiple bilateral unilocular cysts in the mandible and maxilla, along with calcification of anterior part of the falx cerebri. She was eventually diagnosed with Gorlin-Goltz syndrome based on imaging and histopathologic finding of keratocystic odontogenic tumor.